RESEARCH ON THE INVESTMENT AND FINANCING EFFECTS OF BANKRUPTCY RISK-EMPIRICAL RESEARCH FROM CHINA - Ma, Ruifeng (Journal of Buddhist Education and Research (JBER), 2023)
In recent years, cases of corporate bankruptcy due to high corporate bankruptcy risk abound. Based on literature research, this paper uses the data of Chinese listed companies from 2007 to 2020, using the least squares method (OLS) and panel fixed effects.This paper discusses the investment and financing effects of enterprise bankruptcy risk. Through the research, it is found that the enterprise bankruptcy risk has the effect of investment and financing. When the bankruptcy risk increases, the financing constraints of the enterprise will intensify, the excessive debt of the enterprise will expand, and the liquidity risk of the enterprise will increase. The research of this paper not only discusses the impact of changes in corporate bankruptcy risk on micro-enterprises and its transmission mechanism from an empirical level, but also helps to clarify the disputes over corporate bankruptcy risk at the policy level and in practice.